FOCALIZATION FORM IN NOVEL MENCARI PEREMPUAN YANG HILANG BY IMAD ZAKI: NARROTOLOGICAL STUDY - Rendy Pribadi; Ninuk Lustyantie; Zuriyati Zuriyati (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2021)
This research seeks to examine the storytelling elements (storytelling style) in the novel Looking for the Missing Woman by Imad Zaki in the form of dialogue, and the behavior of the characters. There is (finding) a different style when several characters tell their lives, starting from changing characters in storytelling so that they reveal some human traits in this novel. Analysis in narratology tries to reveal this characteristic with three forms of analysis, namely internal and external focalization and external and internal focalization. Internal focalization attempts to describe the dialogue of the